2022
DOI: 10.3390/su141912722
|View full text |Cite
|
Sign up to set email alerts
|

Pertinent Water-Saving Management Strategies for Sustainable Turfgrass in the Desert U.S. Southwest

Abstract: Drought and heat stresses are major challenges for turfgrass management in the desert southwest of the United States where rainfall is insufficient to support managed turfgrass growth. Irrigation water availability and its quality are increasingly strained due to diminishing surface water supplies. Unprecedented drought conditions threaten the reliance on groundwater supplies that are heavily scrutinized for irrigation practices on landscape and recreational turfgrass. Therefore, development of drought toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Many chemical factors of irrigation water influence plant growth directly or indirectly, such as elevated salinity, pH, sodium, bicarbonate, and plant essential nutrients (Chang et al 2020;Harivandi 2004;Porter and Marek 2006;Schiavon et al 2015;Serba et al 2022). Salinity is normally expressed as a measurement of electrical conductivity (EC), which is proportional to the concentration of dissolved ions in water or soil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many chemical factors of irrigation water influence plant growth directly or indirectly, such as elevated salinity, pH, sodium, bicarbonate, and plant essential nutrients (Chang et al 2020;Harivandi 2004;Porter and Marek 2006;Schiavon et al 2015;Serba et al 2022). Salinity is normally expressed as a measurement of electrical conductivity (EC), which is proportional to the concentration of dissolved ions in water or soil.…”
mentioning
confidence: 99%
“…In the US Southwest and Southeast, where climate is characterized as either hot, dry, or both, bermudagrass (Cynodon spp.) is an extensively used turfgrass species, resulting, in part, from its hardiness under hot-dry climatic conditions and improved salinity tolerance (Carrow 1996;Marcum and Pessarakli 2006;Serba et al 2022). Overall, the average evapotranspiration (ET) rate for bermudagrass is 5.51 mmÁd -1 (Colmer and Barton 2017); however, this value can fluctuate depending on environmental evaporative demand, management practice, soil water availability, and, potentially, chemical properties of irrigation sources (Hejl et al 2015;Huang and Fry 1999;Romero and Dukes 2016).…”
mentioning
confidence: 99%
“…Developing sustainable turfgrass varieties has been a major research interest for many university and industry breeders [28,29]. Sustainable turfgrasses have been developed to maintain the appearance and functional aspects of grasses, while minimizing the management cost and enhancing environmental preservation [13,14]. Low-input grasses have been demanded by homeowners because of prolonged droughts in many parts of the world and potential negative environmental externalities caused by the overuse of chemical inputs such as fertilizer, pesticides, and herbicides and weather variability [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study estimates consumers' WTP for low-input and stress-tolerance attributes of warm-season turfgrasses, while considering the potential negative effect of enhancing these attributes on the aesthetics of grasses. Our study focuses on evaluating consumer preferences for sustainability (low-input, stress-tolerance) attributes because earlier studies (e.g., [5][6][7][8][9][10][11][12]) consistently found that turfgrass consumers highly value these attributes and also suggest that it is important to develop turfgrass varieties that require fewer resources, while maintaining visual appeal and functionality (e.g., [13,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Optimal N fertilisation decreases oxidative stress by maintaining osmoprotectants, stimulating antioxidant enzymes and sustaining metabolic activity at reduced tissue water potential, which increases resistance to drought. The availability and quality of irrigation water will decrease due to diminishing supply of surface water around the world [121]. Without additional irrigation, adequate water retention in soil will pose a growing problem in the production of turfgrasses [107].…”
Section: The Use Of Biostimulants In the Production Of Turfgrassesmentioning
confidence: 99%